SHEA/IDSA/APIC Practice Recommendation: Strategies to prevent healthcare-associated infections through hand hygiene: 2022 Update. (8th March 2023) - Glowicz, Janet B.; Landon, Emily; Sickbert-Bennett, Emily E.; Aiello, Allison E.; deKay, Karen; Hoffmann, Karen K.; Maragakis, Lisa; Olmsted, Russell N.; Polgreen, Philip M.; Trexler, Polly A.; VanAmringe, Margaret A.; Wood, Amber R.; et al.
Abstract: The purpose of this document is to highlight practical recommendations to assist acute-care hospitals in prioritization and implementation of strategies to prevent healthcare-associated infections through hand hygiene. This document updates the Strategies to Prevent Healthcare-Associated Infections in Acute Care Hospitals through Hand Hygiene, published in 2014. This expert guidance document is sponsored by the Society for Healthcare Epidemiology (SHEA). It is the product of a collaborative effort led by SHEA, the Infectious Diseases Society of America, the Association for Professionals in Infection Control and Epidemiology, the American Hospital Association, and The Joint Commission, with major contributions from representatives of a number of organizations and societies with content expertise.